JARGON PEDAGANG DI PASAR INDUK BREBES DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA DI SMA - Reni Antika; Leli Triana; Syamsul Anwar (Sasando, 2022)
ABSTRACT Antika, Reni. 2022. Trader’s Jargon in the Brebes Main Market and its implications for Indonesian Language Learning in Senior High Schools. Undergraduate Thesis. Indonesian Language and Literature Education. Faculty of Education and Teacher Training. Tegal University. Advesor I : Leli Triana, S.S., M.Pd. Advesor II : Syamsul Anwar, M.Pd. Keywords : Jargon, Traders,Markets, Implications. This study examines the jargon of traders in the Brebes Main Market and its implications for learning Indonesian in high school. The purpose of this study is to describe the form, the factors-factor causing the use of trader’s jargon in the Brebes Main Market and its implications for learning in high school. This research uses a qualitative approach. The data source is the speech of traders in the Brebes Main Market. The form of data in this study is a sentence related to the jargon of traders in the Brebes Main Market. Data collection was carried out using the tapping technique, which is the basic technique, then an advanced technique was carried out in the form free listening and conversation. Analysis of research data using a pragmatic equivalent method by using a technique of sorting certain elements. The technique of presenting data analysis is in the form of nonformal. The results of the study found (1) a total of 24 data. The form of traders’ jargon in the Brebes Main Market is 11 data noun class consisting of 10 basic nouns and 1derived noun; verbs as much as 4 data consisting of 1 data base verb and 3 derived verbs; adjective as much as 4 data consisting of basic adjectives as much as 4 data; adverb as much as 5 data consisting of basic adverbs of 4 data and derivative adverbs of 1 data. (2) thes factor are setting, participant, and, key, instrument, norma and genre. (3) This research can be implicated in learning Indonesian language in grade 10 senior high school in even semesters in the negotiation text material, namely basic competence (KD) 3.11.